Effect of aqueous extract of Colocasia esculenta against high-fat diet-induced non-alcoholic fatty liver disease in rats: Pharmaceutical Science-Pharmacology for Drug Discovery - Kanala Somasekhar Reddy; Akkiraju Sudheer; PamisettyLikitha Sree; Bhupalam Pradeepkumar; Dharmavaram Deepthi; Chinthaginjala Haranath (International Journal of Life Science and Pharma Research, 2022)
Non-alcoholic fatty liver disease (NAFLD) is becoming a major public health problem due to the increasing incidence of obesity and diabetes in India for the last two decades. The present work is aimed to investigate the effect of aqueous extract of Colocasia esculenta against (AECE) high-fat diet-induced non-alcoholic fatty liver disease in Wistar albino rats. Wistar albino rats were assigned in to four groups as follows; Group I: Normal conventional diet, Group II: High fat diet, Group III & Group IV: Combined high fat diet and different doses of Colocasia esculenta (200 and 400 mg/kg, p.o) for 4 weeks.Treatment with aqueous extract of Colocasia esculenta(200mg/kg, 400mg/kg bw) significantly reduced the body weight and weight gain. In addition, it also significantly reduced the serum triglycerides, total cholesterol, LDL cholesterol, VLDL cholesterol and showed a significant increase in HDL cholesterol as well as significant improvement in liver cholesterol and triglyceride content. AECE treated rats exhibited a significant beneficial effects on levels of liver function markers and oxidative stress and also reversed the histopathological changes.The study suggested the therapeutic potential of AECE against NAFLD, acting in part through anti-obesity, antioxidant mechanisms, and liver marker enzymes.